2011
DOI: 10.1177/0363546511406848
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Exercise Progression for the Gluteus Medius Muscle with Consideration for Iliopsoas Tendinitis

Abstract: This study identified the most appropriate hip rehabilitation exercises for each phase to strengthen the gluteus medius muscle after hip arthroscopy and those to avoid when iliopsoas pain or tendinitis is a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 22 publications
2
61
0
9
Order By: Relevance
“…The gluteus medius muscle has the reduced strength preoperative and length changes postoperative in patients with DDH during THA, Some specific rehabilitation exercise should be designed to strengthen the muscle and keep the stability of hip post-operative as for hip arthroscopy post-operative [37]. Weight-bearing exercises may provide more functional benefit because this type of exercise often activates a greater number of muscle group [38].…”
Section: Discussionmentioning
confidence: 99%
“…The gluteus medius muscle has the reduced strength preoperative and length changes postoperative in patients with DDH during THA, Some specific rehabilitation exercise should be designed to strengthen the muscle and keep the stability of hip post-operative as for hip arthroscopy post-operative [37]. Weight-bearing exercises may provide more functional benefit because this type of exercise often activates a greater number of muscle group [38].…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis has been placed on the hip abductors specifically the gluteus medius because of its role in controlling pelvic stability in the frontal plane [20]. Intramuscular electromyography measuring activation of the gluteus medius compared with the iliopsoas during exercises commonly prescribed following hip arthroscopy has been studied [28]. The results showed that single leg bridging, prone heel squeeze (external rotation isometrics), and side-lying hip abduction with hip internal rotation demonstrate the greatest activity of the gluteus medius and the least of the iliopsoas [28].…”
Section: Early Muscle Activationmentioning
confidence: 99%
“…Intramuscular electromyography measuring activation of the gluteus medius compared with the iliopsoas during exercises commonly prescribed following hip arthroscopy has been studied [28]. The results showed that single leg bridging, prone heel squeeze (external rotation isometrics), and side-lying hip abduction with hip internal rotation demonstrate the greatest activity of the gluteus medius and the least of the iliopsoas [28]. However, long lever hip abduction in side-lying is not recommended during this phase due to the greater joint reactive and compressive force across hip structures occurring with open chain motion [29].…”
Section: Early Muscle Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different protocols have been proposed, but evidence is still poor and there is not a gold standard treatment. As an high iliopsoas muscle activation and a weakness the gluteus medius have been found in many patients, Philippon et al [26] proposed a rehabilitative protocol based on gluteus medius strengthening, which consists into 4 consecutive phases. Garala and Prasad [27] in a retrospective case-control study found better results, according NAHS, after corticosteroids injection compared to iliopsoas tenotomy, and they indicate tenotomy in patients refractory to corticosteroids.…”
Section: Treatment Of Ishsmentioning
confidence: 99%